Effects of a glyphosate-based herbicide on soil animal trophic groups and associated ecosystem functioning in a northern agricultural field - Hagner M; Mikola J; Saloniemi I; Saikkonen K; Helander M (NATURE PUBLISHING GROUP, 2022)
Despite an increasing concern of consequences of using vast amounts of glyphosate-based herbicides in agroecosystems, their potential effects on non-target soil organisms and soil functioning are mostly unknown. It has also been argued that fields in northern latitudes should be under special surveillance as the short active period of decomposers may restrict glyphosate degradation. We investigated the effects of a glyphosate- based herbicide, Roundup, on the abundance of enchytraeids and nematodes, both essential groups in decomposer food webs, and plant litter mass loss and soil availability of mineral N in a two-year agricultural field setting in south-west Finland. Our experiment consisted of (1) non-treated weed plots, (2) plots, where weeds were killed by hoeing, and (3) plots treated with both Roundup and hoeing. We found that killing plants by hoeing had drastic effects on soil fauna and functioning, and apparently, distinguishing these effects from direct glyphosate effects is profoundly important when evaluating glyphosate risks in soils. In contrast, the effects of Roundup on soil fauna and functioning were minor and transient and no glyphosate remains were found in the soil at the end of the experiment. These results suggest that side-effects can be minor and glyphosate degradation effective also in soil under northern climatic conditions.